IMPLIKASI PENDEKATAN INQUIRI TERHADAP PEMAHAMAN MATERI KONSEP GEOGRAFI DENGAN MEMANFAATKAN LINGKUNGAN ADAT KAMPUNG NAGA - Tresa Tri Susilawati, - (2021)
Geography learning in class X SMAN 1 Manonjaya is still rote learning. It can be seen from the data at SMAN 1 Manonjaya, students of class X IPS are lacking in understanding the concept of the essence of geography (geography concepts). The improvement process action was carried out by applying the inquiry learning approach. The formulation of the problem in this study is to measure the level of understanding of students' concepts using the inquiry approach. Data was collected using quantitative methods, the process of data collection using pretest and posttest and direct observation at the location. The results showed that the experimental class using the outdor study method experienced an increase in understanding of the concept with an average score at the time of the pretest was 68.5 and an increase in the posttest with an average of 87.5. Judging from the increase in understanding of the concept of the experimental class students at the level of the interpretation indicator with a gain value of 30.1. In the control class that uses conventional learning with audio-visual media, the average score obtained at the pretest is 48.5 and the post-test is 61.7. Judging from the increase in concept understanding, the experimental class is at the level of the translation indicator with a gain value of 21.00. The implication of the inquiry approach is to apply the inquiry approach by utilizing the environment in the dragon village. This is one of the components that supports the improvement of students 'conceptual understanding of the material and students' concern for the surrounding environment.